1995
DOI: 10.3109/01902149509050835
|View full text |Cite
|
Sign up to set email alerts
|

Clearance in Smaller Airways of Inhaled 6-μm Particles in Subjects with Immotile-Cilia Syndrome

Abstract: In subjects with an inherited lack of mucociliary transport, so called immotile-cilia syndrome (ICS), coughing effectively clears particles deposited in larger airways of the tracheobronchial region. The present study investigated clearance in smaller airways of 111In-labeled 6-microm (aerodynamic diameter) monodisperse Teflon particles in six subjects with ICS. The particles were inhaled at an extremely slow flow, 0.05 L/s. Theoretical calculations and experimental data in healthy subjects using this slow flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
25
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 14 publications
5
25
0
Order By: Relevance
“…King et al [16] stated that samples with higher elasticity cleared less well. An increased amount of mucus seems to improve clearance stated by Svartengren et al [17]. From our studies, we observed that generally an adhesive surface has higher impact and slippery surface has lower impact whereas a dry surface is in-between.…”
Section: Angle With Constant Mucus Simulant Parameterssupporting
confidence: 70%
“…King et al [16] stated that samples with higher elasticity cleared less well. An increased amount of mucus seems to improve clearance stated by Svartengren et al [17]. From our studies, we observed that generally an adhesive surface has higher impact and slippery surface has lower impact whereas a dry surface is in-between.…”
Section: Angle With Constant Mucus Simulant Parameterssupporting
confidence: 70%
“…However, when particles are deposited in small airways, the retained fraction at 72 and 96 h is significantly larger in these patient groups, compared to that of healthy subjects [12,13].…”
mentioning
confidence: 72%
“…Clearance on days 1-7 was larger in the CF patients, 22% (15-29) compared to the healthy subjects, 14% (12)(13)(14)(15)(16). No difference was observed between the CF patients and the healthy subjects in the slow clearance phase at day 7 to day 21, representing small airway clearance.…”
mentioning
confidence: 85%
“…However, studies on mucociliary clearance in patients with PCD are sparse [72][73][74][75][76]. Nasal mucociliary clearance can be used as a screening tool for PCD, even in infants.…”
Section: Radioaerosol Mucociliary Clearance Testsmentioning
confidence: 99%